Diagnosis and Treatment of Drug-Resistant Tuberculosis: State of the Art - Laniado-Laborin, Rafael (Current Respiratory Medicine Reviews, 2017)
Background: For decades there were no significant advances in the development of diagnostic procedures for drug resistant TB (DR-TB), or the availability of new, effective drugs specifically developed for DR-TB. Now, we have witnessed during the last decade, the arrival of several new diagnostic techniques and new drugs, already available for clinical use. This review aims to critically analyze evidence-based recommendations on the most recent developments in the diagnosis and treatment of multidrug-resistant tuberculosis (MDR.TB). Methods: PubMed search for papers describing innovative diagnostic techniques and newer drugs and treatment regimens for MDR-TB. All World Health Organization (WHO) evidence-based guidelines on the subject of diagnostic techniques and new drugs and treatment regimens were also reviewed. Results: 21 papers, 10 WHO guidelines and one Global Tuberculosis Report (2016) were included in the review. Nineteen were original papers on diagnostic techniques or newer drugs and 2 were editorials on the global burden of MDR-TB. One WHO global report dealt with the burden of MDRTB, 6 guidelines had evidence-based recommendations on newer diagnostic techniques for MDR-TB and 4 had evidence based recommendations on new drugs and treatment regimens for MDR-TB. Conclusion: The findings of this review confirm that genotypic diagnostic methods have revolutionized the diagnosis of MDR-TB, from a process that used to take months to one that now takes just a few hours. Also, for the first time in more than 50 years, two new antituberculosis drugs, delamanid and bedaquiline, are now added to the armamentarium, a greatly needed alternative for the treatment of MDR-TB.
Keywords: diagnosis